Electronic-Structures Calculations of Calcium-Intercalated Bilayer Graphene: A First-Principle Study - Sri Hidayati; Iman Santoso; Sefty Yunitasari; Sholihun Sholihun (Indonesian Journal of Chemistry, 2022)
In this study, electronic structure calculations of Ca-intercalated bilayer graphene are conducted using the density functional theory (DFT). We modeled two configurations by positioning calcium in the middle of the bilayer (M-site) and on top of the bilayer surface (T-site). Our results show that the Dirac point is shifted below the fermi level. The approximated critical temperature is 7.9 K. We then calculated the electron transfer and formation energy for each system. We found that, for the M-site, the electron transfer increased as the Ca concentration increased, while the reverse occurred for T-site. The calculated formation energies were negative, meaning that all configurations were spontaneously created. In other words, the involved reactions were exothermic.